Social media opinion and people’s elite of Russia - O. V. Kryshtanovskaya (Цифровая социология)
In modern Russian society, there is a gap be-tween the scientific oncept of “elite” and the group, which is usually called “elite” by the common man. The mass consciousness believes that the word “elite” means something of the highest quality, the best. The ruling group of politicians, in relation to which, as a rule, the term “elite” is used today, does not always look worthy in the eyes of society. Such dissonance, prevailing in the public mind, leads to a contradiction: the elite governing the state exists, but its image does not match the criteria of society. This mental shift in understanding what constitutes the pinnacle of society is very dangerous: after all, people who are disappointed in their state, in their ruling elite, experience frustration, their orientation in the social space is violated, where the concepts of “good and bad”, “top and bottom” are blurred. The question arises, how is it possible to reload the concept of “elite” in public opinion? A group of sociologists conducted an all-Russian research “The People’s Elite of Russia”, which aimed to outline the group of society that Russian citizens are ready to consider elite in the highest sense of the word, whom the Russians respect and whom they are proud of. During 329 personal interviews in 55 subjects of the Federation, we collected the names of people who are holding an impeccable reputation in society. The study included only open-ended questions. During the interview, alist of the names of the “heroes” has been compiled. Then their socio-demographic and professional indicators, political views and values have been analyzed. As a result, a portrait of the “people’s elite” was obtained, the description of which is given in this article.